Evil and Death: Conceptions of the Human in Biblical, Early Jewish, Greco-Roman and Egyptian Literature - Ego, Beate; Mittmann-Richert, Ulrike (Deuterocanonical and cognate literature studies, 2015)
Jewish anthropological beliefs during the Hellenistic-Roman period are an important but previously neglected area of biblical exegesis and Jewish studies. In an effort to address this deficiency, this volume brings together 20 essays related to the subject of sin and death, with special emphasis on integrating material from neighboring cultures. Thus, the volume provides an exemplary foundation for further research on ancient Jewish anthropology.
Keywords: Bible -- Old Testament -- Criticism, interpretation, etc; Theodizee; Menschenbild; Das Böse; Tod; Sünde; Religiöse Literatur; Hellenistische Staaten; Römisches Reich; Ägypten; Bibel; Literatur; Frühjudentum